FACTORS RELATED THE PLAN FOR EXCLUSIF BREASTFEEDING AT THE DIPONEGORO UNIVERSITY FACULTY OF PUBLIC HEALTH STUDENTS - Mona lisa; Bagoes Widjanarko; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The practice of exclusive breastfeeding is strongly influenced by the perception of a mother. The earlier preparation of a prospective mother to plan exclusive breastfeeding, the practice of exclusive breastfeeding in the future is expected to be realized. Diponegoro University's Faculty of Public Health is a faculty whose majority of students are women, who will become future mothers and at the same time have great opportunities to work in the health sector that supports exclusive breastfeeding, should have plans for exclusive breastfeeding. The study aims to determine the factors associated with exclusive breastfeeding plans for students of the Faculty of Public Health, Diponegoro University. This research uses quantitative methods with cross sectional approach. The sample is 100 undergraduate students of Diponegoro University Public Health Sciences. Bivariate analysis using chi square test. The results showed 83% said they planned to give exclusive breastfeeding and 17% said they did not plan. Bivariate analysis results show that there is a correlation between exclusive breastfeeding plans with age (p value 0.027), lecture level (p value 0.026), perception of Suscepbility (p value 0.029), family support (p value 0.019), perception of barrier (p value 0.001 ), and self-efficacy (p value 0.003).While the variable that most influences the perception is perception barrier with an OR value 18,191.Recommended to students of the Faculty of Public Health, Diponegoro University to make the topic of exclusive breastfeeding a subject of discussion among students and with lecturers so as to increase awareness about the importance of exclusive breastfeeding to increase confidence to provide breast milk in the future. And for the Faculty of Public Health to include material related to exclusive breastfeeding in the early study level and also all specializations given the importance of exclusive breastfeeding information.